Going Dirty: The Art of Negative Campaigning - Mark, David (Rowman & Littlefield Publishers, 2009)
Going Dirty is a history of negative campaigning in American politics and an examination of how candidates and political consultants have employed this often-controversial technique. The book includes case studies on notable races throughout the television era in which new negative campaign strategies were introduced, or existing tactics were refined and amplified upon. Strategies have included labeling opponents from non-traditional political backgrounds as dumb or lightweight, an approach that got upended when a veteran actor and rookie candidate named Ronald Reagan won the California governorship in 1966, setting him on a path to the White House. The negative tone of campaigns has also been ratcheted up dramatically since the terrorist attacks of September 11, 2001: Campaign commercials now routinely run pictures of international villains and suggest, sometimes overtly, at other times more subtly, that political opponents are less than resolute in prosecuting the war on terror. The book also outlines a series of races in which negative campaigning has backfired, because the charges were not credible or the candidate on the attack did not understand the political sentiments of the local electorate they were trying to persuade. The effect of newer technologies on negative campaigning is also examined, including blogs and Web video, in addition to tried and true methods like direct mail.